Understanding marketing innovativeness in Asia: a research agenda. Issue 4 (December 2017) - Abosag, Ibrahim; Brennan, David
Abstract Marketing innovativeness has been credited for improvements in general quality of life, consumer experience, and firms' and brands' performance. However, much of the knowledge and research on marketing innovativeness has developed from studies in Western countries, particularly the USA and Europe, with little understanding of marketing innovativeness in Asia. In this paper, we critically examine existing literature with aim of developing a better understanding of marketing innovativeness in Asia. We discuss theoretical and methodological considerations of which researchers need to be aware when they pursue research on Asian countries.